Confirming the explosive dispersal outflow in DR21 with ALMA - Guzmán Ccolque, Estrella (2024)
We present Atacama Large Millimeter/submillimeter Array (ALMA) 1.3 mm continuum and CO (2−1) line emission observationstoward the high-mass star formation region DR21. Five new continuum sources are found. We identify 18 outflow streamers detectedin CO emission that radially arises from a common origin. The velocity spread of the outflow streamers ranges between −100 and+70 km s−1. The radial velocities of each outflow roughly follow linear gradients (Hubble–Lemaître–like expansion motions). Usingthe CO emission of the whole ensemble of streamers, we estimate a total outflow mass of 120–210 M⊙. Additionally, we derivedthe dynamical age (8600 yr), momentum (∼103 M⊙ km s−1), and kinetic energy (∼1048 erg) of the outflow. The morphology andkinematics presented by the CO outflow streamers confirm an explosive dispersal outflow at the heart of DR21. Five dispersal explosiveoutflows associated with massive star-forming regions have been confirmed in our Galaxy (Orion BN/KL, G5.89-0.39, S106-IR,IRAS 16076-5134, and IRAS 12326-6245). However, their occurrence frequency in the Galaxy and their origin are still uncertain.